The Carcinogenic and Non-Carcinogenic Health Risks of Metal(oid)s Bioaccumulation in Leafy Vegetables: A Consumption Advisory - Alsafran, Mohammed; Usman, Kamal; Rizwan, Muhammad; Ahmed, Talaat; Al Jabri, Hareb (Frontiers in Environmental Science, 2021)
High levels of metal(loid)s in soil or food pose a severe health risk to humans. The potential toxicants often find their way into the living systems via the food chain, following bioaccumulation in edible plants, including leafy vegetables grown in or irrigated with contaminated soil or water, respectively. The current study aimed to determine the levels of vanadium (V), chromium (Cr), nickel (Ni), copper (Cu), arsenic (As), lead (Pb), and cadmium (Cd) in leafy vegetables (rocca, coriander, and parsley) grown in different open irrigated farms in Qatar, and investigate their potential human health risks. We found that the mean levels of V, Cr, As, Cd, and Pb were seen to be greater than the recommended WHO/FAO values. The target hazard quotient (THQ) values of Cu and As were found to be greater than 1 for the adult population. For the two elements (i.e., Cu and As), THQ varied from 1.03 to 1.42 and 1.17 to 1.44 in males. In females, the values ranged from 1.20 to 1.65 and 1.35 to 1.55, for Cu and As, respectively. The hazard index (HI) of rocca, coriander, and parsley was 3.99, 4.10, and 4.43, respectively, in males, 4.64, 4.76, and 5.14, respectively, among the female population. The carcinogenic risk (CR) of Cr, Ni, and As ranged from 7.16 × 10-4 to 7.61 × 10-4 , 5.57 × 10-4 to 8.85 × 10-4, and 5.24 × 10-3 to 6.01 × 10-3 respectively in males, whereas, in female, it ranged from 8.31 × 10-4 to 8.83 × 10-4, 6.47 × 10-4 to 1.03 × 10-3, and 6.09 × 10-3 to 6.97 × 10-3, respectively in all vegetables. In crux, the consumption of rocca, coriander, and parsley grown in selected farms in Qatar poses a major health risk (both non-carcinogenic and carcinogenic) to the consumer. As a result, we propose that the safety of vegetables grown in the study area has to be closely monitored